151k views
5 votes
Find the following
(u•w)(2)=
(w•u)(2)=

Find the following (u•w)(2)= (w•u)(2)=-example-1
User Cfedermann
by
6.2k points

1 Answer

3 votes

Answer:


(u \circ w)(2) = -34


(w \circ u) = -49

Explanation:

We are given these following functions:


u(x) = 4x + 2


w(x) = -5x + 1

The first step to solve this question is finding the composite functions. So


(u \circ w)(x) = u(w(x)) = u(-5x+1) = 4(-5x + 1) + 2 = -20x + 6


(w \circ u)(x) = w(u(x)) = w(4x + 2) = -5(4x+2) + 1 = -20x - 9

At x = 2

Now we replace x by 2 in each of the functions. So


(u \circ w)(2) = -20(2) + 6 = -40 + 6 = -34


(w \circ u)(2) = -20(2) - 9 = -40 - 9 = -49

User Lemondoge
by
6.1k points